2022
DOI: 10.3390/nano12213722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Modified Methacrylate-Based Root Canal Sealer in Single-Cone Technique

Abstract: This study aimed to modify EndoREZ with 2.5% dimethylaminododecyl methacrylate (DMADDM) and 1% magnetic nanoparticles (MNP) to study its sealing property, penetration and long-term antibacterial and therapeutic effect in the single-cone technique (SCT) compared with EndoREZ and iRoot SP. Thirty single-root human maxillary premolars were assigned into three groups and obturated with three different root canal sealers by SCT. Every specimen was then scanned using micro-CT to analyze void fraction, and void volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Other metal or metal oxide NPs are also of interest as materials that could be added into existing root canal sealers. One recent study incorporated ferrimagnetic magnetite (Fe 3 O 4 ) NPs (50 to 100 nm) and a quaternary ammonium salt (QAS) into EndoREZ sealer [ 132 ]. By applying an external magnetic field, dentinal tubule penetration was enhanced.…”
Section: Nanomaterials As Endodontic Sealersmentioning
confidence: 99%
“…Other metal or metal oxide NPs are also of interest as materials that could be added into existing root canal sealers. One recent study incorporated ferrimagnetic magnetite (Fe 3 O 4 ) NPs (50 to 100 nm) and a quaternary ammonium salt (QAS) into EndoREZ sealer [ 132 ]. By applying an external magnetic field, dentinal tubule penetration was enhanced.…”
Section: Nanomaterials As Endodontic Sealersmentioning
confidence: 99%
“…The addition of dimethylaminododecyl methacrylate (DMADDM) into different dental materials can improve antibacterial effects against pathogens and biofilms. Another group has aimed to modify EndoREZ with DMADDM and magnetic nanoparticles (MNPs) [ 195 ]. The modification can lead to good sealing performance, penetration, and long-term antibacterial properties.…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%
“…However, the AgNPs used did not improve the bacterial leakage resistance of the AH plus sealer after 3 months of observation [ 193 ]. Nanoparticles of ZnO were also added to the original sealer and this modification inhibited biofilm formation within the sealer– dentin interface, reduced cytotoxicity, and improved physicochemical properties [ 195 ]. It was concluded that the addition of ZnO NPs into a calcium hydroxide-based sealer shows better antibiofilm efficacy than CSNPs against E. faecalis .…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%